Genericization of Trademarks: Brand Name becomes Generic Name - A Challenge for Brand Managers - Shafiulla, B. (Indian Journal of Marketing, 2010)
A successful trademark can help a company build a strong franchise that can be licensed, sold, or used in brand extension. Many consumer product manufacturers, faced with an increasing financial risk in entering new markets, are using established brand names to facilitate such entries (Aaker and Keller 1990). The major assets of any Company are its trademarks, therefore, companies spend billions to promote their brands or Trademarks to increase their brand equity and make their brands "Household Names" or "Top-of-the-Mind Brands". But if customers use these names as generic names from being applied to any product beside their names, then they have to spend millions more to prevent these Trademarks from becoming Genericized Trademarks. Coca Cola and Xerox are probably the best known global brands facing this challenge globally. The process by which intellectual property in trademark is diminished or lost typically occurs over a period of time as a result of common use of trademark in a market place, where a trademark falls into disuse entirely, or where a trademark owner doesn't enforce its rights through law suits or actions for passing off or trademark infringement. When a brand name or trademark becomes a generic name, it is termed as "Genericide or Genericized Trademark or Generic Descriptor or Trademarkicide" but these are not technical terms. Experts have suggested various terms, like in Plasticolor Molded Products Vs Ford Motor Co., who called genericide a "malapropism" i.e. unintentional misuse of a word by confusion with one that is similar and suggested genericization. A member of Cecil Adams's contributing board suggested genericide as "Brand Eponym". However, in legal literature till date, only genericide has been used for all such cases.